DETERMINAN KUALITAS PELAYANAN, HARGA SERTA LOKASI PADA KEPUASAN KONSUMEN BENGKEL GARAGE MANUAL TECH NGANJUK - Mahendra, Danang; Wihara, Dhiyan Septa; Soeprajitno, Edy Djoko (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The study was conducted to determine whether the effect of partial (t) or jointly (F) on service quality, price and location on consumers of the Nganjuk Garage Manual Technician Workshop. The research approach is quantitative, research techniques are cause-and-effect. The population of consumers who have come directly to the Nganjuk Manual Tech Garage Workshop. This research has a sample of 40 respondents, namely people who are not limited, with sampling that is accidental sampling, namely anyone who happens to meet the researcher at the location. The data analysis technique used instrument test, descriptive analysis, classical assumption test, multiple linear analysis, determination test and hypothesis testing using SPSSv23 software. The results of the study stated that service quality, price, and location had a significant effect partially (t) or jointly (F) on consumer satisfaction at the Nganjuk Tech Garage Manual.